Academic Senate Minutes 2005-11-10 - Academic Senate:::::::::
Report of the Chair. Agenda approve. Minutes of 10/27/05 approved. Update on WASC. Course Outline Policy amended and approved. Resolution endorsing SAC's Advising Survey - First Reading. Media Access to Senate-Talk discussion, further action postponed. Provost report.